Dénètem Touam Bona, Fugitive, where are you running? - Israel, Paolo (Kronos, 2024)
D. Touam Bona, Fugitive, Where are you Running?, L. Hengehold (trans) (Cambridge, UK: Polity Press, 2023), 230 pp., ISBN: 978-1509551842 Fugitive, Where are you Running? is a collection of essays, most of which were previously published in French, by writer, philosopher and curator Dénètem Touam Bona. The author's inclination to straddle geographic and conceptual lines is reflected in the scope, exuberance and poetic verve of the volume. The first three chapters ('Return of the Maroni', 'The Art of the Fugue', 'Manhunt') lay the conceptual foundation by foregrounding categories of marronage, fugitivity and fugue. The fugitive slave is presented as the figure that haunts the establishment of capitalist modernity and the only possible 'line of flight' from it. The fugue is the art of subtle evasion from the prisons of racialised capitalism and an alternative to the triumphalist politics of armed liberation struggles. Touam Bona proposes an impressionistic, rhapsodic and allegorical travel through the various incarnations of the maroon community - with its spontaneous and horizontal modes of organisation and accretion - and capitalism's death drive to surveil and suppress them. The following two chapters track the iterations and repression of fugitivity in the present, by engaging with technologies of migrant surveillance at the border ('Heroic Land', which mixes critique and fiction) and the space of Mayotte, a French department in the heart of the Indian Ocean, increasingly securitised and excised from the histories of flux that characterise this region ('The Impossibility of an Island'). The sixth chapter ('Cosmo-poetics of the Refuge') returns to the book's central theme of the maroon rebellion, connecting it to Afro-diasporic spirituality and performance. The final extended chapter ('Liana Dreaming') turns to environmental concerns, by foregrounding the figure of the liana as the point of resistance to colonial penetration and weapon of maroon resistance. In Caribbean cultures, the liana and the vine bring together collective bodies and communities. Against colonial tropes of taming, erasure and penetration, the power of the forest itself generates plant-induced visions of unsubmission.